Importance of spindle speed in ring frame - Redwanul Islam, Md.; Chakrabortty, Amit; Ghosh, Joyjit; Iqbal, Tareq; Tanvir Hossen, Md. (International Journal of Engineering and Technology, 2021)
In textile industries, spinning sector plays a vital role because this sector produces the main raw material for the textile industries which is known as yarn. So for getting good qualities garments, it is needed to ensure the good qualities yarn. There are many things which are re-sponsible for producing good qualities yarn. Among these spindle speed is an important thing. One must have to change the spindle speed, when he changes the count. As every count has a particular spindle speed in which the production shows maximum production efficiency. Here we used five most commonly used yarn counts in the maximum factories. The counts are 15 Ne, 20 Ne, 25 Ne, 30 Ne and 40 Ne. We analyzed these counts with different speed and found that every count showed maximum efficiency at a particular spindle speed. The out-come of this paper is applicable in all types of ring frame machine , especially for producing single carded and combed yarn.Â Â